2015
DOI: 10.1093/jnci/djv324
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Low Accrual in the National Cancer Institute’s Cooperative Group Clinical Trials

Abstract: Background:The extent to which trial-level factors differentially influence accrual to trials has not been comprehensively studied. Our objective was to evaluate the empirical relationship and predictive properties of putative risk

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
88
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(92 citation statements)
references
References 18 publications
3
88
1
Order By: Relevance
“…As a result, investigators may overestimate the availability of eligible patients and underestimate the challenges in actually accruing those patients. A recent analysis found that greater accrual competition, in the form of more trials in the same disease setting, and fewer available patients were significant predictors of low accrual in NCI group trials (13). A more feasible method of estimating the number of patients eligible, able, and potentially willing to participate in any given trial is needed.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, investigators may overestimate the availability of eligible patients and underestimate the challenges in actually accruing those patients. A recent analysis found that greater accrual competition, in the form of more trials in the same disease setting, and fewer available patients were significant predictors of low accrual in NCI group trials (13). A more feasible method of estimating the number of patients eligible, able, and potentially willing to participate in any given trial is needed.…”
Section: Introductionmentioning
confidence: 99%
“…This puts increasing pressure on the current research system, as large numbers of patients are required to assess relevance or superiority before their implementation into clinical practice. This warranted large number greatly exceeds the amount of patients that currently participate in clinical trials (5-15%) [14][15][16]. Low recruitment rates may also imply selective inclusion of patients in trials rather than representative population samples [17], which may result in limited external validity of outcomes.…”
mentioning
confidence: 99%
“…However, this design in itself is often not only complicated by slow recruitment rates and limited generalizability [15], it is also subject to a considerable delay between conceptualization and start, limited long-term follow-up, inadequate collection of patient-reported outcomes (PROMs), high non-completion rates and high costs [16]. An innovative alternative proposed for the classic RCT is the 'cohort multiple randomized controlled trial' (cmRCT) [20].…”
mentioning
confidence: 99%
“…Only 3/22 (14%) were accruing at less than half the rate planned, a benchmark for triggering a formal review of studies sponsored by National Cancer Institute (NCI)’s Cancer Therapy Evaluation Program. While this is similar to cooperative group oncology trials (14), selective reporting of quantitative imaging trials that had better accrual may have occurred. In addition, a group heavily invested in quantitative imaging research (ie, the NCI’s QIN) may have the expertise required for optimizing the chances of successful accrual.…”
Section: Discussionmentioning
confidence: 62%